Auctioning Long-Term Projects under Financial Constraints - Arve, M; Martimort, D (Review of Economic Studies, 2025)
Abstract We consider a procurement auction for the provision of a basic service to which an add-on must later be appended. Potential providers are symmetric, have private information on their cost for the basic service and the winning firm must also implement the add-on. To finance value-enhancing activities related to the add-on, this firm may need extra funding by outside financiers. Nonverifiable effort related to these activities creates a moral hazard problem which makes the firm’s payoff function for the second period concave in returns over the relevant range. Concavity has two effects. First, it makes it more attractive to backload payments to facilitate information revelation. Second, uncertainty on the cost of the add-on introduces a background risk which requires a risk premium. In this context, we characterize the optimal intertemporal structure of payments to the winning firm, equilibrium bidding behaviour and reserve prices for a first-price auction.